Therapeutic drug monitoring for either oral or intravenous busulfan when combined with pre- and post-transplantation cyclophosphamide. Issue 3 (3rd March 2016) - Lombardi, Lindsey R.; Kanakry, Christopher G.; Zahurak, Marianna; Durakovic, Nadira; Bolaños-Meade, Javier; Kasamon, Yvette L.; Gladstone, Douglas E.; Matsui, William; Borrello, Ivan; Huff, Carol Ann; Swinnen, Lode J.; Brodsky, Robert A.; et al.
Abstract: Busulfan (Bu)/cyclophosphamide (Cy) is a standard conditioning platform for allogeneic transplantation. We developed a strategy separating the Cy into two pre/post-transplantation doses (PTCy), providing myeloablative conditioning and single-agent graft-versus-host disease (GVHD) prophylaxis. We investigated the impact of Bu route on treatment-related toxicity for 131 consecutive adult patients. Busulfan was administered in four daily divided doses either orally ( n  = 72) or intravenously ( n  = 59) with pharmacokinetics on the first-dose and as necessary on subsequent doses to achieve a target area-under-the-concentration-curve (AUC) of 800–1400  μ mol*min/L per dose. BuCy/PTCy with pharmacokinetics is well-tolerated with low treatment-related toxicity. Hepatic veno-occlusive disease incidence was 6% with two fatal events. Bu administration route in the context of BuCy/PTCy did not statistically impact hepatotoxicity, GVHD, relapse, disease-free survival, or overall survival. The BuCy/PTCy platform has a low incidence of treatment-related toxicity, including hepatotoxicity, in hematologic malignancies when using pharmacokinetics for a target AUC of 800–1400  μ mol*min/L, irrespective of Bu administration route.